2011
DOI: 10.1002/pbc.23121
|View full text |Cite
|
Sign up to set email alerts
|

Career burnout among pediatric oncologists

Abstract: Approximately three quarters of pediatric oncologists experience burnout. Further research is needed on the effectiveness of interventions aimed at preventing and treating work-related burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
85
4
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 56 publications
5
85
4
2
Order By: Relevance
“…Despite there is no global level of burnout, some authors refer to a high level of burnout for those subjects with at least one high scale. 17,18 The importance of the definition lays in the comparability of the results with those of other works. We decided to adopt this form of analysis to charac- 19 Different variables haven been proposed as predisposing factors for burnout: gender, prolonged working hours and little sleep, among others.…”
Section: Discussionmentioning
confidence: 92%
“…Despite there is no global level of burnout, some authors refer to a high level of burnout for those subjects with at least one high scale. 17,18 The importance of the definition lays in the comparability of the results with those of other works. We decided to adopt this form of analysis to charac- 19 Different variables haven been proposed as predisposing factors for burnout: gender, prolonged working hours and little sleep, among others.…”
Section: Discussionmentioning
confidence: 92%
“…Pediatric subspecialists also have level of stress that raises significant concerns. [9][10][11] Although many published studies have described the prevalence of burnout in pediatric settings, to our knowledge the factors that contribute to burnout have not been documented.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, males, junior residents, and those working in the university hospital were at increased risk of burnout syndrome. Other authors found females at higher risk of developing burnout in an oncology study [17]. This may not apply to other rotations that deal with less life threatening illnesses.…”
Section: Discussionmentioning
confidence: 82%
“…Affected pediatric residents may develop negative attitudes toward self and professional activity, and eventually lose interest in pediatric care, have low productivity, and self-esteem. Routine exercise should be encouraged and promoted as it is associated with lower burnout scores [17] [24]. Physicians who are satisfied with their lives outside of work are also less likely to have burnout.…”
Section: Discussionmentioning
confidence: 99%